Behavioral Neurobiology of the Endocannabinoid System - Kendall, Dave; Alexander, Stephen (Current Topics in Behavioral Neurosciences, 2009)
The endocannabinoid signalling system is one of the key modulators of central nervous function. This volume provides timely and in-depth coverage of the roles of the endocannabinoid signalling system in the neurobiology of behavior. It is essential reading for any researcher with a background in neuroscience wanting to know more about the endocannabinoids. The first section provides a comprehensive account of the component parts of the system (the signalling molecules, synthetic and degradative enzymes and receptors), their location within the central nervous system and the endocannabinoids' roles in neural plasticity. This section also describes the toolboxes (genetic and pharmacological) used to study the system. The second section concentrates on endocannabinoid function in the control of normal physiological behaviors including a reference to the evolution of the system based on its operation in non-mammalian vertebrates. The volume concludes by addressing the importance of the endocannabinoids in pathological behaviors including affective and cognitive disorders, neurodegenerative conditions, feeding and drug abuse.